OPERATION CHARACTERISTICS OF ONE-HAND-OPERATED WHEELCHAIRS - UEMATSU, Mitsutoshi (Journal of The Showa Medical Association, 2000)
To clarify operation characteristics of various types of one-hand-operated wheelchairs, three experiments were carried out using a standard type wheelchair (type S), 4 types of one-hand-operated wheelchairs, 1 type of double-hand-rim type wheelchair (type W), and 3 types of lever type wheelchairs (types L1, L2, L3) . In experiment 1, the velocity, number of strokes, number of running off the track, relative metabolic rate (RMR), and heart rate during driving at a comfortable pace and the maximum pace were compared. In experiment 2, (1) the time needed to perform 7 driving and operational tasks, number of strokes, and stability on straight runs were evaluated ; in addition, the subjective exercise intensity, regions of fatigue, and difficulty of operation were measured conducted (10 healthy subjects), and (2) the ease of operation by a care-giver was compared among the lever type wheelchairs. In experiment 3, the time of slalom driving and the degree of independence in moving around in the hospital were compared after 1-week practice of wheelchair operation (19 elderly disabled subjects) . (1) The velocity of driving at a comfortable pace was similar to the velocity of walking by hemiplegic patients in all types of wheelchairs, and the RMR was less than that during “moderate exercise”, but the heart rate immediately after a run at a comfortable pace was higher in types W and L1 than in the other types. (2) The ease of operation in executing driving tasks was best in type S, followed by types L2, L3, L1, and W in this order. In type L1, the efficiency of transmission of force was poor, the velocity was slow, and the number of strokes was high. In type L3, the difficulty of transfer was large, but the transmission of force was good, and the velocity was the highest in runs on slopes. The ease of manipulation by a care-giver was relatively good in type L1, but considerable improvements were needed in all L types. (3) Independent moving in the hospital was considered possible when the time of a one 5 m shuttle slalom run is about 1 minute or less. Independence was often achieved fastest in patients who could drive the type S wheelchair only as slowly as the type W wheelchair when they used type L wheelchairs. Palpitation and pain of the upper limbs were often reported by those who used type L wheelchairs. From these results, type S is considered to be suitable for patients with good residual abilities, and type L for those with poor residual abilities. In particular, type L1 is considered to be appropriate for those with reduced upper limb muscle strength and coordination, type L3 for those who retain considerable upper limb muscle strength and have needs for outdoor operations, and type L2 for patients in an intermediate category. Type W was the least fit, and it, along with type L1, should be applied carefully to patients with cardiac disorders. These indications should be considered in selecting one-hand-operated wheelchairs for individual patients.